Ellas se van. Mujeres migrantes en Estados Unidos y España - González Montes, Soledad (Migraciones Internacionales, 2017)
Martha Judith Sánchez e Inmaculada Serra, coords., 2013, México, D. F., Instituto de Investigaciones Sociales-Universidad Nacional Autónoma de México, 993 pp.